Can Elevated Air [CO2] Conditions Mitigate the Predicted Warming Impact on the Quality of Coffee Bean? - Ramalho, José C.; Pais, Isabel P.; Leitão, António E.; Guerra, Mauro; Reboredo, Fernando H.; Máguas, Cristina M.; Carvalho, Maria L.; Scotti-Campos, Paula; Ribeiro-Barros, Ana I.; Lidon, Fernando J. C.; DaMatta, Fábio M. (Frontiers in Plant Science, 2018)
Climate changes, mostly related to high temperature, are predicted to have major negative impacts on coffee crop yield and bean quality. Recent studies revealed that elevated air [CO2] mitigates the impact of heat on leaf physiology. However, the extent of the interaction between elevated air [CO2] and heat on coffee bean quality was never addressed. In this study, the single and combined impacts of enhanced [CO2] and temperature in beans of Coffea arabica cv. Icatu were evaluated. Plants were grown at 380 or 700 μL CO2 L-1 air, and then submitted to a gradual temperature rise from 25 ºC up to 40 ºC during ca. 4 months. Fruits were harvested at 25 ºC, and in the ranges of 30-35 ºC or 36-40 ºC, and bean physical and chemical attributes with potential implications on quality were then examined. These included: colour, phenolic content, soluble solids, chlorogenic, caffeic and p-coumaric acids, caffeine, trigonelline, lipids, and minerals. Most of these parameters were mostly affected by temperature (although without a strong negative impact on bean quality), and only marginally, if at all, by elevated [CO2]. However, the [CO2] vs. temperature interaction strongly attenuated some of the negative impacts promoted by heat (e.g., total chlorogenic acids), thus maintaining the bean characteristics closer to those obtained under adequate temperature conditions (e.g., soluble solids, caffeic and p-coumaric acids, trigonelline, chroma, Hue angle, colour index), and increasing desirable features (acidity). Fatty acid and mineral pools remained quite stable, with only few modifications due to elevated air [CO2] (e.g., phosphorous) and/or heat. In conclusion, exposure to high temperature in the last stages of fruit maturation did not strongly depreciate bean quality, under the conditions of unrestricted water supply and moderate irradiance. Furthermore, the superimposition of elevated air [CO2] contributed to preserve bean quality by modifying and mitigating the heat impact on physical and chemical traits of coffee beans, which is clearly relevant in a context of predicted climate change and global warming scenarios.